PENAPISAN ISOLAT FUNGI MIKORIZA ARBUSKULAR INDIGENUS RIZOSFIR PISANG SEBAGAI INDUSER KETAHANAN TANAMAN PISANG CAVENDISH TERHADAP LAYU FUSARIUM (Fusarium oxysporum f.sp. cubense) - Eri Sulyanti; Trimurti Habazar; Eti Farda Husin; Nasril Nasir; Abdi Dharma (Universitas Lampung, 2011)
Using biological agents to control fusarium wilt is still not maximal result, based on that need to search a potensial indigeneous biological agents specific location. The experiment conducted to study the role biological agents of arbuscular mychorrhizal fungi indigenous to control fusarium wilt diseases. Twenty four isolates were evaluated for the potensials to reduced fusarium wilt incidence. This research was arranged by Randomized Block Design (RBD) on green house experiment. The aim of this research is to investigate the ability of arbuscular mychorrhizal fungi isolates to reduce fusarium wilt on banana seedling. The results showed that all arbuscular mychorrhizal fungi isolates indigenous from healthy banana rhizosphere reduced fusarium wilt development and increase banana growth.Three isolates (Gl1KeP4, Gl1BuA4, Gl2BuA 6) could control Fusarium wilt until 100% with longer incubation periode and lower disease of banana seedlings as Plant Growth Promoting Fungi. Key words: Arbuscular Mychorrhizal Fungi Indigenous, Fusarium Wilt, Musa sp